Isoenzyme specific PFK-2/FBPas-2 inhibition as an anti-cancer strategy - Williams, J (2013)
High aerobic glycolytic capacity is correlated with poor prognosis and increased tumour aggressiveness. 6Phosphofructo-1-kinase catalyses the first irreversible step of glycolysis, and is activated by fructose-2,6-bisphosphate, a product of the kinase activity of four bifunctional isoenzymes, 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase (PFK-2/FBPase-2:PFKFB1-4). These are potential anti-tumour targets, but their individual and collective role requires further investigation. This thesis had three aims; to validate the PFK-2/FBPase-2 isoenzymes as anti-cancer targets, to investigate the requirement for isoenzyme-specific targeting, and to initiate assay development, enabling future identification of novel inhibitors. A panel of cancer cell lines was examined and PFKFB3 and PFKFB4 were confirmed to be the most strongly induced isoenzymes in hypoxia, regulated by HIF-1α. Basal and hypoxic relative PFKFB3/PFKFB4 expression varied markedly, and three cell lines with varying expression ratios (MCF-7, U87, PC3) were selected for further study. siRNA knockdown of each isoenzyme individually, markedly reduced 2D and 3D cell growth. The effect of PFKFB3 knockdown was consistently more pronounced, particularly in hypoxia. Double PFKFB3/PFKFB4 knockdown was significantly less effective than PFKFB3 knockdown alone. Direct antagonism of PFKFB3 and PFKFB4 on F-2,6-BP concentration was observed, with PFKFB3 exhibiting high kinase activity, as anticipated, and PFKFB4 exhibiting high bisphosphatase activity. The degree of antagonism was dependent on the relative PFKFB3/PFKFB4 expression ratio. Extensive efforts were made to examine the wider metabolic effect of PFKFB3/PFKFB4 on flux towards glycolysis or the pentose phosphate pathway (PPP), including using metabolite, lipid droplet, 13C NMR and mass spectrometry assays. No significant change in metabolic flux was detected, the evidence presented therefore suggesting the impact of the antagonistic effects of the isoenzymes on [F-2,6-BP] extends beyond regulation of metabolic flux alone. This study concluded that the most effective therapeutic strategy will be one that involves a PFKFB3-specific inhibitor, preferably hypoxia-targeted. Accordingly, steps were taken to validate and optimise a robust medium-throughput assay system.